2017
DOI: 10.1038/s41598-017-17965-z
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Glomerular Filtration Rate, Proteinuria, and Risk of Cardiovascular Diseases and All-cause Mortality in Diabetic Population: a Community-based Cohort Study

Abstract: Data about associations between estimated glomerular filtration rate (eGFR) and proteinuria with cardiovascular diseases (CVDs) and all-cause mortality among diabetic population is less described. We aimed to describe these associations in Chinese diabetic population, and investigate the difference between sexes. The study was based on 8,301 diabetic participants in the Kailuan study, who was free of CVDs at baseline. We used Cox proportional hazard models to examine the associations of eGFR and proteinuria wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
(33 reference statements)
1
6
0
Order By: Relevance
“…We showed that 24 h proteinuria was an independent predictor of cardiocerebrovascular events, which is consistent with previous reports [24][25][26][27]. Higher aldosterone and lower α-klotho levels tended to be accompanied by a higher incidence of cardiocerebrovascular events, but this was not statistically significant.…”
Section: Discussionsupporting
confidence: 91%
“…We showed that 24 h proteinuria was an independent predictor of cardiocerebrovascular events, which is consistent with previous reports [24][25][26][27]. Higher aldosterone and lower α-klotho levels tended to be accompanied by a higher incidence of cardiocerebrovascular events, but this was not statistically significant.…”
Section: Discussionsupporting
confidence: 91%
“…Proteinuria results in undernutrition and inflammation, which are associated with poor outcomes in patients with chronic disease, even in the general population. 34 Importantly, patients with MM and a low AGR should be assessed for the presence of a strong inflammatory response, malnourishment, or both. Treatment with nutritional support and anti-inflammatory agents might reduce the risk of mortality in patients with MM.…”
Section: Discussionmentioning
confidence: 99%
“…A low AGR could be the consequence of transcapillary albumin loss [26], such as proteinuria. Proteinuria was associated with an increased risk for cardiovascular events and acute cerebrovascular disease, even in the general population [27,28]. Therefore, patients with low AGR may indicate vascular damage.…”
Section: Discussionmentioning
confidence: 99%